Analysis of physical and thermodynamic properties of poly(2-phenyl-1,3-dioxolane-4-yl-methyl-methacrylate-co-styrene) polymer with inverse gas chromatography - Karagöz, MH; Zorer, ÖS; Ilter, Z (Taylor & Francis Inc, 2006)
In this study, physical and thermodynamic properties of poly(2-phenyl-1,3-dioxolane-4-yl-methyl-methacrylate-co-styrene) (PDMMA-ST) were investigated by using inverse gas chromatography. Two groups of solvents with different chemical natures and polarities were used to obtain information about PDMMA-ST-solvent interactions: alcohols and alkanes. The specific retention volume (V-g(0)), the sorption enthalpy (Delta H-1(S)), sorption free energy (Delta G(1)(S)), sorption entropy (Delta S-1(S)), the weight fraction activity coefficients of solute probes at infinite dilution (Omega(infinity)(1)), and Flory-Huggins interaction parameters (chi(infinity)(12)) between polymer and solvents were determined for the interactions of PDMMA-ST with alcohols and alkanes by inverse gas chromatography in the temperature range of 333-473 K. Also, the solubility parameters of PDMMA-ST at infinite dilution were found by plotting the graph of [(delta(2)(1)/RT) - chi(infinity)(12)/V-1] versus solubility parameters, delta(1), of probes.
Keywords: polymer; thermodynamic properties; inverse gas chromatography